Multi‐segment foot kinematics during gait following ankle arthroplasty. Issue 3 (20th May 2021) - Fritz, Jessica M.; Canseco, Karl; Konop, Katherine A.; Kruger, Karen M.; Tarima, Sergey; Long, Jason T.; Law, Brian C.; Kraus, Jonathan C.; King, David M.; Harris, Gerald F.
Abstract: Ankle arthritis is a debilitating disease marked by pain and limited function. Total ankle arthroplasty improves pain while preserving motion and offers an alternative to the traditional treatment of ankle fusion. Gait analysis and functional outcomes tools can provide an objective balanced analysis of ankle replacement for the treatment of ankle arthritis. Twenty‐nine patients with end‐stage ankle arthritis were evaluated before and after ankle arthroplasty. Multi‐segment foot and ankle kinematics were assessed annually following surgery (average 3.5 years, range 1–6 years) using the Milwaukee Foot Model and a Vicon video motion analysis system. Functional outcomes (American Orthopedic Foot and Ankle Society [AOFAS] ankle/hindfoot scale, short form 36 [SF‐36] questionnaire) and temporal‐spatial parameters were also assessed. Kinematic results were compared to findings from a previously collected group of healthy ambulators. AOFAS and SF‐36 mean scores improved postoperatively. Walking speed and stride length increased after surgery. There were significant improvements in tibial sagittal range of motion in terminal stance and hindfoot sagittal range of motion in preswing. Decreased external rotation of the tibia and increased external rotation of the hindfoot were noted throughout the gait cycle. Pain and function improved after ankle replacement as supported by better outcomes scores, increased temporal‐spatial parameters, and significant improvement in tibial sagittal range of motion during terminal stance and hindfoot sagittal range of motion during preswing. While multi‐segment foot kinematics were improved, they were not restored to control values. Statement of clinical significance: Total ankle arthroplasty does not fully normalize mutli‐segment gait kinematics despite improved patient‐reported outcomes and gait mechanics.